REVIEW PAPER Non-alcoholic steatohepatitis (NASH) - Fehér, János; Németh, Eszter; Lengyel, Gabriella (Archives of Medical Science, 2005)
Metabolic syndrome is one of the most frequent diseases of our age, and it is accompanied by numerous complications. Clinical studies have been published suggesting that, in addition to the already well-known consequences of the metabolic syndrome, hepatic involvement should also be taken into consideration in a significant part of cases. Fatty liver or in most cases the histological picture of non-alcoholic steatohepatitis can mainly be observed in metabolic syndrome. These conditions may develop into hepatic cirrhosis, hepatic failure, or even hepatocellular cancer. The more components of the metabolic syndrome are present, and the more severe they are, the higher the likelihood of this transition is to happen. All these facts underscore the importance of assessing the hepatological status in patients with the metabolic syndrome.